Plasma PGFM and progesterone concentrations, luteolysis moment and estrous cycle length in Nelore cows submitted to uterine biopsies - Martin, I.; Membrive, C. M.B. [UNESP]; Vettorato, L. F.; Binelli, M.; Oba, E. [UNESP]; Ferreira, J. C.P. [UNESP] (FapUNIFESP (SciELO), 2015)
In this study, endometrial samples were collected in 14 Nelore cows on days zero (ovulation), five, nine, thirteen and nineteen of the estrous cycle (biopsy group), and in 15 females these collections weren't performed (control group). Biopsies were done on the uterine horn endometrium contralateral to the ovary with corpus luteum. Blood samples were taken at -24, -16, -8, 0 +8, +16 and +24 hours in relation to progesterone drop (<1ng/mL, zero moment) and evaluated for 13, 14-dihydro-15-keto prostaglandin F2-alpha (PGFM) by radioimmunoassay (RIA). Plasma progesterone concentration was determined by RIA every 24 hours. Data were analyzed by ANOVA using the PROC GLM and MIXED of the SAS. The mean value for PGFM during the entire period evaluated was greater in the biopsy group. The mean concentration of PGFM at moment zero was not different between the groups; the mean concentration of PGFM was higher in the biopsy group before and after the drop in progesterone level. The maximum mean concentration observed was not different between the groups; however, the mean minimum concentration was different with high values in the biopsy group. Although the PGFM concentrations were higher in the biopsy group, the biopsy and control groups had similar length of estrous cycle showing that repeated endometrial biopsy on the side contralateral to the ovary with corpus luteum does not affect luteolysis and the length of the estrous cycle.
Keywords: 13,14-dihydro-15-keto prostaglandin F2-alpha; Bovine; Corpusluteum; Endometrium; Progesteronic phase